Seed dormancy and germination in tree tomato (Solanum betaceum Cav.) and lulo (Solanum quitoense Lam.) - Torres-González, Alba Marina (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
Tree tomato (Solanum betaceum Cav.) and lulo (Solanum quitoense Lam.) fruits enjoy high consumption and commercialization in Colombia. Seed dormancy has been reported for both species, and their propagation depends on seeds. The optimal germination conditions for these species are not well known. Thus, the temperature regimes for the seed germination were based on the mean, minimum and maximum temperatures of the locations where the crops were grown. Germination tests were carried out in four replicates of 50 seeds each on Petri dishes for both crops. Six temperature conditions and four pre-treatments were evaluated to break the seed dormancy for several seed lots. S. betaceum and S. quitoese exhibited shallow seed dormancy, and less dormancy was detected in the commercialized cultivars, such as S. betaceum cv. Tamarillo and S. quitoense (i.e. common lulo). For both species, the most recently harvested seeds had more germination capacity than the seeds stored for several months at a low seed moisture content (4%) and low storage temperature (20°C). The seed dormancy of S. betaceum and S. quitoense was broken successfully by applying GA3 (2,000 mg L-1) or alternating temperatures (e.g. 25/15°C). However, both treatments at the same time did not provide an additional benefit to promote seed germination. Potassium nitrate (1%) promoted seed germination in the S. betaceum seeds at both constant and alternating temperatures and in the S. quitoense seeds, only when alternating temperatures were applied. The application of GA3 increased the rate of germination more than KNO3 for both species at all temperatures. Using any of these treatments would work well to break seed dormancy in S. betaceum and S. quitoense, and the most convenient option could be selected depending upon budget and other resources.